Salmonella Distribution, Adaptation, Control Measures and Molecular Technologies - Annous, Bassam A.; Gurtler, Joshua B. (IntechOpen, 2012)
The discovery of Salmonella in swine in 1885 marked the beginning of intense efforts to control salmonellae that have continued for the past 127 years. The majority of foodborne outbreaks are caused by only a few of the 2500+ known serovars. While progress has been made on many fronts, salmonellosis has yet to be eliminated in either developed or in developing nations. This work represents the collective contributions of authors from all around the world. Chapters in this book address a wide array of topics related to understanding and controlling this pathogen, including: Salmonella as studied in the environment, air and in food products; virulence and pathogenicity; control by bacteriophages and other antimicrobials; bacterial adaptation; etc.